(untitled) (Ames, Iowa, 2007)
Whole Grains and Health presents a science-based discussion of whole grains and their expanding role in health and disease. An international collection of authors presents current perspectives on grains, the many opportunities for further research into whole grains and the remarkable growth potential for product development. Coverage includes discussions on the health benefits of a diet rich in whole grains, the functional components of whole grains and the regulatory nuances of labeling grain products
Keywords: Health,Grain,Grain in human nutrition,Cereals,Các loại hạt,Ngũ cốc và sức khỏe; Giá trị sử dụng; Therapeutic use